2007
DOI: 10.1152/ajplung.00250.2006
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Toll-like receptor signaling in the pulmonary host response toPseudomonas aeruginosa

Abstract: Activation of pulmonary defenses against Pseudomonas aeruginosa requires myeloid differentiation factor 88 (MyD88), an adaptor for Toll-like receptor (TLR) signaling. To determine which TLRs mediate recognition of P. aeruginosa, we measured cytokine responses of bone marrow cells from wild-type mice and mice lacking TLR2 (TLR2−/−), TLR4 (TLR4−/−), TLR2 and TLR4 (TLR2/4−/−), or MyD88 (MyD88−/−) to wild-type P. aeruginosa and to fliC P. aeruginosa, which lacks the TLR5 ligand flagellin. Mice also were challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
129
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 69 publications
12
129
1
7
Order By: Relevance
“…We and others have previously shown that TLR4 [23,42] as well as TLR5 [24,43] is also involved. Differential engagement of PRR involved in P. aeruginosa recognition could depend on the site or the time of infection and the prevailing microbial ligand.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We and others have previously shown that TLR4 [23,42] as well as TLR5 [24,43] is also involved. Differential engagement of PRR involved in P. aeruginosa recognition could depend on the site or the time of infection and the prevailing microbial ligand.…”
Section: Discussionmentioning
confidence: 81%
“…In murine experimental models of lung infection triggered by P. aeruginosa, TLR signaling seems redundant in the pulmonary host response [24,25], suggesting potential involvement of another receptor in the host defense against P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in a model of post-influenza pneumococcal pneumonia. 20 Similarly, TLR2 null mice did not show increased mortality or developed pneumonia after challenge with the Gram-negative pulmonary pathogen P. aeruginosa by aerosol, 21 indicating that other signaling pathways in addition to TLR2/MyD88 signaling are evidently involved in responses to these pulmonary pathogens.…”
Section: Tlr2 In Airway Infectionmentioning
confidence: 99%
“…[32][33][34][35] MyD88 null mice have a more defined phenotype upon bacterial infection than null mice for any of the individual TLRs. 21,36 This suggests that multiple TLRs contribute to the host response to certain organisms, or that other receptors not yet identified can signal through MyD88 and participate in responses to bacterial infection.…”
Section: Tlr5 In Airway Infectionmentioning
confidence: 99%
“…Moreover, studies have suggested the role of TLR5 in induction of an early innate response and of T2SS and T3SS, in death, due to Pseudomonas infection in mouse lung infection model [18,26,27]. …”
Section: Introductionmentioning
confidence: 99%